Reducing the Risk of Groundwater Contamination by Improving Household Wastewater Treatment - Herbel, Kevin L.; Powell, Morgan G.; Greene, Julia M. (My University, 1998)
Properly installed and maintained systems for treating and disposing of household wastewater minimize impact of the system on groundwater and surface water.
EP38_1998-08
Keywords: EP38; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP